ANALYSIS ON THE IMPLEMENTATION OF DIGITAL MARKETING TRIFECTA STRATEGY IN SOCIAL MEDIA MARKETING (CASE STUDY: BRAND GOâS INSTAGRAM) - Nurul Hanindita, Annisa
Social media networks have become an essential part of a company's media mix. Social media is so diverse that it can be used in any way that best suits a company’s objectives. Keeping up with an increasingly fragmented media landscape can be difficult for consumers as they are forced to compare all content marketing offerings. However, digital marketers recognize that many types of content marketing fit into three media types known as the digital marketing trifecta. The digital marketing trifecta is a combination of paid media, owned media, and earned media. For various reasons, social media marketing covers all three media of the trifecta approach. Social media marketing is the most adaptable digital marketing channel that can influence paid media, owned media, and earned media, marketers can effectively maintain a presence on social media, efficiently deliver paid advertising, and build a brand for the company. Brand GO is a new growing-up-milk brand that utilizes social media platforms to help maximize their reach and efficiently execute their digital marketing strategy. They leverage digital marketing trifecta as a framework in guiding them to focus their social media marketing strategy on paid media, owned media, and earned media. The use of the three media must be done synergistically to produce an effective strategy with this framework. The right synergy varies depending on the company’s goals. Thus, this brand needed an evaluation to see the areas of improvement in implementing social media marketing with the trifecta approach. Methodology used in this research is qualitative case study, with two techniques of data collection: primary data through interviews and secondary data from Brand GO’s official data records. This research found that in implementing digital marketing trifecta, from the perspective of Brand GO’s overall social media performance, Brand GO’s social media marketing strategy has managed to produce an effective result. However, from the perspective of social media content category performance target, not all content categories produce an effective result due to lack of emotional bond. In conclusion, Brand GO does not have any problems in the application of its paid media. Meanwhile, there is still substantial room for improvement in the application of their earned media and owned media. Therefore, application of emotional branding that has not yet been explored by Brand GO is recommended for further development of owned and earned media.